2022
DOI: 10.1111/pbi.13827
|View full text |Cite
|
Sign up to set email alerts
|

R gene triplication confers European fodder turnip with improved clubroot resistance

Abstract: Summary Clubroot is one of the most important diseases for many important cruciferous vegetables and oilseed crops worldwide. Different clubroot resistance (CR) loci have been identified from only limited species in Brassica, making it difficult to compare and utilize these loci. European fodder turnip ECD04 is considered one of the most valuable resources for CR breeding. To explore the genetic and evolutionary basis of CR in ECD04, we sequenced the genome of ECD04 using de novo assembly and identified 978 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 113 publications
0
28
0
Order By: Relevance
“…Genetic analysis and fine mapping studies have identified major loci, quantitative trait loci (QTLs) and genes from different Brassica species involved in P. brassicae resistance (Hasan, Shaikh, et al, 2021;Lv et al, 2020). Due to the lack of CR genes in B. napus (canola, genome AACC) germplasm, the canola progenitor B. rapa (Chinese cabbage, genome AA) is considered as a major source in CR breeding (Huang et al, 2017;Yang et al, 2022).…”
Section: Club Root Re S Is Tan Cementioning
confidence: 99%
See 2 more Smart Citations
“…Genetic analysis and fine mapping studies have identified major loci, quantitative trait loci (QTLs) and genes from different Brassica species involved in P. brassicae resistance (Hasan, Shaikh, et al, 2021;Lv et al, 2020). Due to the lack of CR genes in B. napus (canola, genome AACC) germplasm, the canola progenitor B. rapa (Chinese cabbage, genome AA) is considered as a major source in CR breeding (Huang et al, 2017;Yang et al, 2022).…”
Section: Club Root Re S Is Tan Cementioning
confidence: 99%
“…Several candidate CR genes have been identified to encode NLR proteins in B. rapa (Hatakeyama et al, 2017(Hatakeyama et al, , 2022Huang et al, 2017;Matsumoto et al, 2012;Wang et al, 2022;Yang et al, 2022;Zhang et al, 2021). CRa and Crr1a were successfully iso- and CRA8.1b, and those three genes could be responsible for the clubroot resistance, the TIR-NBS-LRRs BraA08g039211E…”
Section: Club Root Re S Is Tan Cementioning
confidence: 99%
See 1 more Smart Citation
“…Two genes encoding TNL proteins and one candidate gene encoding RLP protein were the most probable candidate genes responsible for clubroot resistance in DingWen (DW). Again, the same locus PbBa8.1 was fine mapped in the ECD04 (most valuable resources for CR breeding) genome and narrowed down into a 1428 Kb region and nine candidate genes were identified in this region [ 103 ]. Functional analysis of one candidate gene, CRA8.2.4 , with NBS-LRR domain revealed that the plants with higher expression of CRA8.2.4 were not infected with clubroot.…”
Section: Genomicsmentioning
confidence: 99%
“…Furthermore, very recently, one candidate gene, named CRA3.7.1 , identical to CRa from B . rapa T136-8 [ 121 ] and CRb _α [ 122 ] was functionally characterized by Yang et al [ 103 ]. B .…”
Section: Genomicsmentioning
confidence: 99%